2007
DOI: 10.1017/s1368980007334071
|View full text |Cite
|
Sign up to set email alerts
|

Hunger in young children of Mexican immigrant families

Abstract: Objective: To measure rates of hunger and food insecurity among young US-born Latino children with Mexican immigrant parents (Latinos) compared with a nonimmigrant non-Latino population (non-Latinos) in a low-income clinic population. Design, setting and subjects: A repeated cross-sectional survey of 4278 caregivers of children ,3 years of age in the paediatric clinic of an urban county hospital for a 5-year period from 1998 to 2003. A total of 1310 respondents had a US-born child with at least one parent born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 26 publications
3
40
2
4
Order By: Relevance
“…The difference in obesity by English language use at home disappeared after adjusting for SES, suggesting that Ethnicity & Health 519 low SES was likely to underlie the higher prevalence of obesity among children in non-English-speaking households. Low SES is known to be associated with poor diet choices, food insecurity (Kaiser et al 2002, Kersey et al 2007, and food stamps (Dinour et al 2007) which are related to increased risk for obesity (US Department of Health and Human Services 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in obesity by English language use at home disappeared after adjusting for SES, suggesting that Ethnicity & Health 519 low SES was likely to underlie the higher prevalence of obesity among children in non-English-speaking households. Low SES is known to be associated with poor diet choices, food insecurity (Kaiser et al 2002, Kersey et al 2007, and food stamps (Dinour et al 2007) which are related to increased risk for obesity (US Department of Health and Human Services 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Second, caregivers' level of nutrition knowledge, access to nutrition information, and attitudes to child diet and health can strongly influence feeding practices and the types of foods their children are fed (Coveney, 2005). It is known that the circumstances of international migration, accompanied by social exclusion and poverty, can put children at risk of limited access to a nutrientdense diet and also places stress on families (Chilton et al, 2009;Hadley, Zodhiates, & Sellen, 2007;Kersey, Geppert, & Cutts, 2007).…”
Section: Relation To Previous Studies Of Newcomer Feeding Decisionsmentioning
confidence: 99%
“…In a study of legal immigrants in California, Texas, and Illinois, Kasper et al [2000] found that predictors of hunger were income below federal poverty level, receipt of food stamps, Latino ethnicity, and poor English. Children of Mexican immigrant families are at greater risk of child hunger than non-Latinos [Kersey et al, 2007]. Mazur et al [2003] found that among Latino households with children, food insecurity was positively associated with both lower levels of acculturation and income.…”
Section: Introductionmentioning
confidence: 99%